THE EFFECTS OF THREE DIFFERENT REAR KNEE ANGLES ON KINEMATICS IN THE SPRINT START - Milanese, C.; Bertucco, M.; Zancanaro, C. (Biology of Sport, 2014)
The purpose of this study was to investigate the rear knee angle range in the set position that allows sprinters to reach greater propulsion on the rear block during the sprint start. Eleven university-track team sprinters performed the sprint start using three rear knee angle conditions: 90°, 115° and 135°. A motion capture system consisting of 8 digital cameras (250 Hz) was used to record kinematic parameters at the starting block phase and the acceleration phase. The following variables were considered: horizontal velocity of the centre of mass (COM), COM height, block time, pushing time on the rear block, percentage of pushing time on the rear block, force impulse, push-off angle and length of the first two strides. The main results show that first, horizontal block velocity is significantly greater at 90° vs 115° and 135° rear knee angle (p<0.05 and p<0.001 respectively) at block clearance and the first two strides; second, during the pushing phase, the percentage of pushing time of the rear leg is significantly greater at 90° vs 135° rear knee angle (p<0.01). No significant difference was found for block time among the conditions. These results indicate that block velocity is the main kinematic parameter affected by rear knee angle during the starting block phase and acceleration phase. Furthermore, the 90° rear knee angle allows for a better push-off of the rear leg than larger angles at the set position. The findings of this study provide some direction and useful practical advice in defining an efficient rear leg biomechanical configuration at the set position.